EXPERIMENTAL STUDY OF SPUN PILE TO PILE CAP CONNECTION CONFINED BY STEEL JACKET - Lase, Yuskar; Mulia Orientilize; Widjojo Adi Prakoso; Sidiq Purnomo; Ignatius Harry Sumartono (GEOMATE Journal, 2024)
The high confinement ratio requirement for precast piles, according to ACI 318-19 with tight-spaced spiral reinforcement, is difficult to implement. A certain amount of reinforcement is necessary from the pile adjacent to the pile cap to ensure the occurrence of a plastic hinge during a severe earthquake. To address the deficiency of the confinement ratio, an economical solution, such as the customization of steel jackets, is suggested instead of increasing the amount of spiral reinforcement in the spun pile. An experimental study was conducted to investigate the performance of the spun pile and pile cap connection with the steel jacket. The jacket was fabricated from a steel plate aligned to the diameter of the spun pile, with rivets to connect it’s end. Three specimens with different connection details were tested through cyclic loading. The connection of the steel jacket and the bonding between the pile and the jacket were found to be two crucial factors influencing the pile connection behavior. Although the jacket was not specifically designed to enhance the bending capacity of the connection, the embedment into the pile cap influenced the overall strength of the connection. The presence of the steel jacket increases the bending strength by 18%. Additionally, the jacket improves the connection’s deformability and boosts the energy dissipation capacity by 1.8 times compared to a connection without the steel jacket. The study revealed that the steel jacket can be used as a promising alternative solution to fulfill the confinement of the spun pile on the connection area.